The glitch force. Vol. 1, Attack of the killer bunnies : an unofficial graphic novel for Minecrafters - Miller, Megan, 1963- (New York : Sky Pony Press, 2023)
The Glitch, an elite task force, is sent into the dark forest where they must risk their lives to stop a deceptively adorable army of killer bunnies with glowing red eyes and an uncontrollable appetite for destruction.
K-3
2.4
Keywords: Minecraft (Game) -- Comic books, strips, etc; Video games -- Comic books, strips, etc; Rabbits -- Comic books, strips, etc; Forests and forestry -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Graphic novels; Comics (Graphic works)